Investigation on Satisfaction with Caravans Through User Experiences - Kayan, Ali Oytun (Eastern Mediterranean University, 2024)
This Republic of Northern Cyprus. The study focuses on the design and functionality of caravans, evaluating their impact on user satisfaction through graphical analysis. Surveys conducted indicate the presence of eight distinct caravan regions in Northern Cyprus, with six of them deemed suitable for observation. Discussions with municipalities revealed some imposing bans on caravan users in designated areas, contributing to a decline in caravan culture. A survey conducted in the identified six regions assessed the perspectives and satisfaction levels of caravan users. Additionally, map analysis and field studies were integral components of this research. The literature review provides a comprehensive overview of existing research on mobile spaces, user experience, and satisfaction. Data collected from surveys shed light on user satisfaction regarding caravan organization, generating recommendations for caravan designs by posing questions about layout, design, and functionality. Indepth interviews enriched the study by providing a deeper understanding of user experiences and perspectives on caravan organization. The findings of this research will be presented in three main sections: caravan organization, user satisfaction with caravan organization, and recommendations for enhancing user satisfaction through improvements in caravan organization and design. The study offers valuable insights for caravan manufacturers and designers to understand user needs, potentially influence regulations, and improve the functionality and design of caravans. Keyword: caravan, compact space, mobility, user experience, spatial organization, satisfaction

Bu tez, Kuzey Kıbrıs Türk Cumhuriyeti'nde karavan organizasyonu ile kullanıcı memnuniyeti arasındaki ilişkiyi araştırmayı amaçlamaktadır. Çalışma, karavanların tasarım ve işlevselliği üzerine odaklanmış, bu unsurların kullanıcı memnuniyetine etkisini grafiklerle değerlendirmiştir. Yapılan anketler, Kuzey Kıbrıs Türk Cumhuriyeti'nde 8 farklı karavan bölgesi olduğunu ortaya koymuş ve bu bölgelerin 6 tanesinin gözlemlenmesi için uygun olduğunu belirtmiştir. Belediyelerle yapılan görüşmeler, bazı belediyelerin karavan kullanıcılarını ağırlayan bölgelerde konaklamayı yasaklama kararı aldığını göstermiş, bu da karavan kültürünün gerilemesine neden olmuştur. Belirlenen 6 farklı bölgede yapılan anket çalışması, karavan kullanıcılarının perspektiflerini ve memnuniyet düzeylerini değerlendirmiştir. Harita analizi ve arazi incelemesi de bu çalışmanın önemli adımları arasında yer almıştır. Literatür taraması, mobil alanlar, kullanıcı deneyimi ve memnuniyet konularındaki mevcut araştırmalara genel bir bakış sunmuştur. Yapılan anketler, karavan organizasyonu ile ilgili kullanıcı memnuniyeti hakkında veriler toplamış, düzen, tasarım ve işlevsellikle ilgili sorular sorularak karavan tasarımlarıyla ilgili öneriler sunulmuştur. Ayrıca, derinlemesine yapılan görüşmeler, kullanıcı deneyimleri ve karavan organizasyonu üzerine daha derinlemesine bir anlayış kazanılmasına katkı sağlamıştır. Çalışmanın bulguları üç ana bölümde analiz edilip sunulacaktır: karavan organizasyonu, karavan organizasyonuna yönelik kullanıcı memnuniyeti ve karavan organizasyonunu ve tasarımını geliştirmek için kullanıcı memnuniyetini artırmaya yönelik öneriler. Bu çalışma, karavan üreticileri ve tasarımcıları için kullanıcı ihtiyaçlarına ve beklentilerine daha iyi yanıt verebilmek, belediyelere karavan konaklamasıyla ilgili referans sağlayabilmek ve karavanların işlevselliğini ve tasarımını iyileştirmek için önemli içgörü ve öneriler sunmayı amaçlamaktadır. Anahtar Kelimeler: karavan, kompakt alan, hareketlilik, kullanıcı deneyimi, alan organizasyonu, memnuniyet
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2024. Supervisor: Prof. Dr. Kağan Günçe
Keywords: Thesis Tez; Mobile homes; recreational vehicles; and caravans; Interior Architecture; Functionality; organization of caravans; Caravans; Interior architecture; User satisfaction; Human factors in design; Compact living; Recreational vehicles; Environmental design